Worshipping Patron Saints: Ethnological Research in Croatia - Belaj, Marijana (Array, 2009)
The author presents selected outcomes from her research on belief in patron saints in Croatia. The emphasis is placed on contexts in which such beliefs are manifested, on the ways in which they are expressed and on the significance that believers appear to attribute to patron saints. The analysis of these questions is based on the nature and forms of relationship to patron saints on two levels: community religiosity, and individual religiosity. At community level, patron saints are not only associated with the economic betterment, but are also given a significant role with respect to the identity formation of a given community and its social life. At the level of individual religiosity, the patron saint is seen as a personal protector who is called on at various moments in life, which leads to the annulment of the acknowledged “ specialization” of the different saints. The author outlines a number of guidelines for the future research into this and associated topics, primarily the research of sacred places and the processes involved with their consecration.